The Effect of Oxytocin Massage on Breast Milk Production in Postnatal Mothers - Nurhusna H. Umar; Nila Widya Keswara (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Breast milk production during the postpartum period is a crucial factor in successful breastfeeding and achieving exclusive breastfeeding. However, during the early postpartum period, many postpartum mothers experience difficulties in breast milk production, influenced by physical and psychological conditions. One non-pharmacological intervention that can be used to help facilitate breast milk production is oxytocin massage, which aims to stimulate the release of the hormone oxytocin and increase the let-down reflex. This study aims to analyze the effect of oxytocin massage on breast milk production in postpartum mothers at the Marisa Community Health Center. This study used a quantitative pre-experimental design with a one-group pretest–posttest approach. The study sample consisted of 30 postpartum mothers selected using purposive sampling according to the inclusion criteria. Breast milk production was measured before and after the oxytocin massage intervention using a structured observation sheet with units of milliliters (ml). Data analysis was performed using univariate and bivariate methods. Normality was tested using the Shapiro–Wilk test, while differences were tested using the Wilcoxon signed-rank test. The results showed that the average milk output before oxytocin massage was 18.00 ± 5.95 ml, and increased to 51.83 ± 10.94 ml after the intervention. The Wilcoxon test showed a p-value of 0.000 (p < 0.05), indicating a significant effect of oxytocin massage on increasing breast milk output. It was concluded that oxytocin massage is effective as a non-pharmacological intervention to increase breast milk production in postpartum mothers and can be integrated into postpartum care in primary health care services.